Role of IgM Memory B Cells and Spleen Function in COVID-19 - Rossi, Carlo Maria; Lenti, Marco Vincenzo; Merli, Stefania; Di Sabatino, Antonio (Frontiers in Immunology, 2022)
Memory B cells, along with plasma cells, originating in germinal centres contribute to broad and long-lasting protection from SARS-CoV-2 and are therefore an ideal target of vaccine strategies aimed at improving the immune response against the virus. Recent evidence, mainly boosted by studies on spleen function/involvement in COVID-19, seems to support the notion that also extrafollicular memory B cells exert a relevant role, particularly in the acute setting of the infection. Herein we critically summarise the current landscape of studies on memory B cells, focusing on the IgM memory subset, by comparing COVID-19 with other hypo- and asplenic conditions and by adding recent data on follow-up studies. The detection and management of patients with impaired IgM memory B cell response and spleen hypofunction may contribute to their better care and prognosis.